Features of efficient schemes of complex-shaped forging stamping in an open die designed using numerical simulation - A. V. Vovchenko; K. A. Kostenko; O. I. Katrich (Advanced Engineering Research)
Introduction. The die stamping (DS) process of the compound cross-section in an open die is considered. The work objective is to determine the form and number of operating steps to obtain the limiting conditions by the adopted parameters. During the investigation, the following lower parameters are determined: uneven strained condition of the considered section of the finished forging; metal consumption on the forging flashes; relative length of the stage of stamping finishing (metal flow only to the flash).Materials and Methods. The study is based on the use of the numerical finite element method (FEM) for the solution to direct and inverse problems of the component forming under die forging. QForm package is used as a software tool.Research Results. It is shown that the metal consumption can be reduced from 13-17% of the forging volume in the selected section to the values of 1.8 to 3.5%. The relative length of the stamping finishing stage can be reduced from 17% to 0.4%. The nonuniformity of the distribution of the cumulative deformation along the cross-section is estimated by the corresponding criterion. It can be reduced to the limits typical for optimization-level tasks (when using a profile piece-part) or a level of rational values (under the introduction of a single blanking pass).Discussion and Conclusions. The quantification of stamping processes considered in this paper can be applied in the generalized type to any form of DS products. This allows improving the quality of forgings and significantly reducing their production cost.